2004
DOI: 10.1016/j.jacc.2003.09.045
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of short- and long-term outcomes after off-pump and on-pump coronary artery bypass graft surgery with sternotomy

Abstract: On-pump patients experience better long-term survival and freedom from revascularization than off-pump patients. However, the survival benefit from on-pump procedures was no longer present in the last two years of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
3
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 43 publications
(22 reference statements)
5
58
3
6
Order By: Relevance
“…In one initial phase of the experiment, the occurrence of arrhythmia and hemodynamic instability is expected even during the preparation of anastomoses in the anterior wall, which, with experience, rarely happens even when three or four grafts into the lateral and posterior heart walls are necessary. Studies suggest a great benefit of off-pump surgeries compared to conventional surgeries [24][25][26], which are already giving good results over the medium term [27][28][29]. With the greater advances in interventionist cardiology, the heart surgeon is put under great pressure to use less invasive surgery and provide excellent results, which, we believe, start with offpump surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…In one initial phase of the experiment, the occurrence of arrhythmia and hemodynamic instability is expected even during the preparation of anastomoses in the anterior wall, which, with experience, rarely happens even when three or four grafts into the lateral and posterior heart walls are necessary. Studies suggest a great benefit of off-pump surgeries compared to conventional surgeries [24][25][26], which are already giving good results over the medium term [27][28][29]. With the greater advances in interventionist cardiology, the heart surgeon is put under great pressure to use less invasive surgery and provide excellent results, which, we believe, start with offpump surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Dos de los tres fallecidos correspondieron a conversiones a cirugía con bomba, Las otras complicaciones observadas (infarto perioperatorio, accidente cerebrovascular, mediastinitis, hemorragia postoperatoria) fueron comparables a las observadas en cirugía con bomba 26,27 .…”
Section: Resultados Inmediatosunclassified
“…Exceptuando por la necesidad de revascularización, la mayoría de los autores concuerdan en que los resultados alejados son comparables entre ambas técnicas 22,[26][27][28][29] .…”
Section: Resultados Alejadosunclassified
“…A more recent study (18) conducted from 1999 to 2000 using the same database found a survival benefit with OPCAB (OR 0.83), especially in high-risk subgroups. In New York state, a cohort study (19) of OPCAB in 1997 to 2000 found no difference in hospital mortality compared with ONCAB. In addition, this study found that after three years of follow-up, OPCAB patients had a survival disadvantage (hazard ratio 1.086) (19).…”
mentioning
confidence: 98%
“…In New York state, a cohort study (19) of OPCAB in 1997 to 2000 found no difference in hospital mortality compared with ONCAB. In addition, this study found that after three years of follow-up, OPCAB patients had a survival disadvantage (hazard ratio 1.086) (19). This analysis, when limited to a more recent subgroup (1999 to 2000), showed no difference in the two-year mortality rates of ONCAB and OPCAB (19).…”
mentioning
confidence: 98%